2004
DOI: 10.1088/0967-3334/25/5/018
|View full text |Cite
|
Sign up to set email alerts
|

Activity-based sleep–wake identification in infants

Abstract: Actigraphy offers one of the best-known alternatives to polysomnography for sleep-wake identification. The advantages of actigraphy include high accuracy, simplicity of use and low intrusiveness. These features allow the use of actigraphy for determining sleep-wake states in such highly sensitive groups as infants. This study utilizes a motion sensor (accelerometer) for a dual purpose: to determine an infant's position in the crib and to identify sleep-wake states. The accelerometer was positioned over the sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 25 publications
2
39
1
1
Order By: Relevance
“…PS is the predicted probability of sleep. Sazonov et al (2004) reported the following performance with their algorithm: 75.4% accuracy, 93.2% sensitivity, 41% specificity.…”
Section: Sazonovõs Algorithmmentioning
confidence: 93%
See 4 more Smart Citations
“…PS is the predicted probability of sleep. Sazonov et al (2004) reported the following performance with their algorithm: 75.4% accuracy, 93.2% sensitivity, 41% specificity.…”
Section: Sazonovõs Algorithmmentioning
confidence: 93%
“…In this section, we will describe how one can apply two previously reported actigraphy algorithms (Sadeh et al, 1994;Sazonov et al, 2004) to the CHIME data set. These two algorithms use linear combinations of features computed from the actigraphic signal to distinguish sleep from wake.…”
Section: Linear Combination Methodsmentioning
confidence: 99%
See 3 more Smart Citations